2001
DOI: 10.2527/2001.79123158x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calendar date and summer management on the in situ dry matter and fiber degradation of stockpiled forage from bermudagrass pastures.

Abstract: Limited information is available that describes the disappearance kinetics of bermudagrass (Cynodon dactylon L. Pers.) during fall and early winter. Five ruminally cannulated, crossbred steers (387 +/- 18.3 kg) were used to determine the effects of calendar date and previous summer management on the in situ degradation kinetics of DM and NDF for forage clipped from stockpiled 'Greenfield' bermudagrass pastures. Forage was stockpiled at two sites following summer hay or pasture management, and samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 0 publications
9
28
0
Order By: Relevance
“…Forage quality can also be subject to the fibre characteristics of forage (Scarbrough et al, 2001), because the nutritive value of forages for ruminants highly depends on the ratio between cell content and cell walls and on the ability of the rumen microorganisms to degrade the plant cell walls (Waldo, 1986). The fibre fraction makes up an important part of the ruminant diet and originates mainly from plant cell walls that consist of a variety of structural polysaccharides, often cross-linked with proteins and phenolic components, particularly with lignin, which is also prevalent in the cell wall.…”
mentioning
confidence: 99%
“…Forage quality can also be subject to the fibre characteristics of forage (Scarbrough et al, 2001), because the nutritive value of forages for ruminants highly depends on the ratio between cell content and cell walls and on the ability of the rumen microorganisms to degrade the plant cell walls (Waldo, 1986). The fibre fraction makes up an important part of the ruminant diet and originates mainly from plant cell walls that consist of a variety of structural polysaccharides, often cross-linked with proteins and phenolic components, particularly with lignin, which is also prevalent in the cell wall.…”
mentioning
confidence: 99%
“…In contrast, autumn stockpiling is a management technique in which forage is allowed to accumulate throughout the late summer and early fall for subsequent grazing throughout the late fall and winter. Recently, there has been increased interest in the utilization of autumn‐stockpiled standing bermudagrass for this purpose (Lalman et al, 2000; Scarbrough et al, 2001). Stockpiled forages can provide winter pasture for grazing livestock, thereby reducing the need for supplemental hay and its associated costs (Adams et al, 1994; D'Souza et al, 1990; Hitz and Russell, 1998).…”
mentioning
confidence: 99%
“…Previously, Lalman et al (2000) suggested that the digestibility and concentrations of crude protein in stockpiled bermudagrass are generally adequate to meet the nutritional requirements of spring‐calving cows during the first few weeks after frost. Scarbrough et al (2001) suggested that this forage should be used in northern Arkansas during a relatively short (60‐d) window between mid‐October and mid‐December; after that time, the nutritive value becomes very poor. However, autumn‐stockpiled bermudagrass potentially could fill an important niche in the upper South by providing forage in mid‐ to late autumn when many producers in the region are allowing tall fescue ( Festuca arundinacea Schreb.)…”
mentioning
confidence: 99%
“…1, daylength data in Fig. Tifton 85 samples were dried at 50°C for at least 72 h (Scarbrough et al, 2001), composited by date and shipped to Texas A&M AgriLife Research-Beeville, and ground using a Wiley mill (Arthur H. Thomas Company, Philadelphia, PA) to pass through a 4-mm screen before incubation. 3.…”
Section: Forage Collectionmentioning
confidence: 99%
“…Tifton 85 forage samples at different dates represented similar leaf:stem components (visually). Tifton 85 samples were dried at 50°C for at least 72 h (Scarbrough et al, 2001), composited by date and shipped to Texas A&M AgriLife Research-Beeville, and ground using a Wiley mill (Arthur H. Thomas Company, Philadelphia, PA) to pass through a 4-mm screen before incubation. This grind size was a deviation from Vanzant et al (1998), who recommended grinding samples to 2 mm, but has been used by Foster et al (2011).…”
Section: Forage Collectionmentioning
confidence: 99%